2022
DOI: 10.1002/asia.202200569
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Generation from Organic Hydrides under Continuous‐Flow Conditions Using Polymethylphenylsilane‐Aluminum Immobilized Platinum Catalyst

Abstract: Hydrogen is an important resource for realizing the goal of a hydrogen‐based society as well as for synthetic organic chemistry. Catalytic dehydrogenation of organic hydrides such as methyl cyclohexane is attractive for hydrogen storage and transportation in terms of reversibility and selectivity of catalytic reactions and hydrogen storage density. We developed a highly active polymethylphenylsilane‐aluminum immobilized platinum catalyst (Pt/MPPSi‐Al2O3) for dehydrogenation of organic hydrides. Organic hydride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Therefore, significant efforts have been devoted to the development of hydrogen extraction and utilization methods using MCH as a promising material for hydrogen storage applications [29][30][31][32][33][34][35][36]. Kobayashi et al reported the continuous-flow hydrogenation reaction of olefins using H₂ gas extracted from MCH under a parallel catalyst cartridge system, which continuously generated H₂ gas from a heterogeneous Pt catalyst-packed cartridge, and a solution of a substrate possessing an olefin moiety flowed into another heterogeneous Pd catalyst-packed cartridge [37].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, significant efforts have been devoted to the development of hydrogen extraction and utilization methods using MCH as a promising material for hydrogen storage applications [29][30][31][32][33][34][35][36]. Kobayashi et al reported the continuous-flow hydrogenation reaction of olefins using H₂ gas extracted from MCH under a parallel catalyst cartridge system, which continuously generated H₂ gas from a heterogeneous Pt catalyst-packed cartridge, and a solution of a substrate possessing an olefin moiety flowed into another heterogeneous Pd catalyst-packed cartridge [37].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, significant efforts have been devoted to the development of hydrogen extraction and utilization methods using MCH as a promising material for hydrogen storage applications [29][30][31][32][33][34][35][36]. Kobayashi et al reported the continuous-flow hydrogenation reaction of olefins using H 2 gas extracted from MCH under a parallel catalyst cartridge system, which continuously generated H 2 gas from a heterogeneous Pt catalyst-packed cartridge, with a solution of a substrate possessing an olefin moiety flowing into another heterogeneous Pd catalyst-packed cartridge [37].…”
Section: Introductionmentioning
confidence: 99%